2014
DOI: 10.1088/1757-899x/63/1/012157
|View full text |Cite
|
Sign up to set email alerts
|

Twinning induced nanostructure formation during cryo-deformation

Abstract: Abstract. In the present work the influence of cryo-rolling to a true strain ε=2.66 on twinning and formation of ultrafine-grained/nanostructure in commercial-purity titanium and Fe-0.3C-23Mn-1.5Al TWIP steel was quantified using scanning and transmission electron microscopy. Different influence of twinning on the kinetics of microstructure refinement and nanostructure formation in titanium and steel was revealed. In titanium twin boundaries during deformation transform into arbitrary high-angle grain boundari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…It can be therefore concluded that the contribution of grain refinement in the investigated material is less important for the overall strengthening compared to the increased dislocation density. Similar results were obtained for different TWIP steels rolled to 80-90% at room temperature [17,36,37].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It can be therefore concluded that the contribution of grain refinement in the investigated material is less important for the overall strengthening compared to the increased dislocation density. Similar results were obtained for different TWIP steels rolled to 80-90% at room temperature [17,36,37].…”
Section: Discussionsupporting
confidence: 84%
“…Due to a different dependence of the critical resolved shear stress of twinning and slip on deformation temperature, the intensity of twinning can be increased by decreasing the deformation temperature. Some preliminary results have shown the positive effect of very low temperature of 77 K on the microstructure refinement in TWIP steel during large deformation [17]. However, further investigations in this direction for a better understanding of the correlation between deformation conditions and microstructure evolution are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the overall character of the microstructure evolution and mechanical properties of the HEA is rather similar to that observed for other low-SFE fcc alloys e TWIP steels [24,36], including very high ductility due to twinning and higher contribution of substructure strengthening. Being one of the main deformation modes in both alloys twinning supports quite high strain hardening and relatively low dislocation density at the initial stages of deformation.…”
Section: Discussionsupporting
confidence: 69%
“…The strengthening by warm rolling is accompanied by a decrease in plasticity, although rather large uniform elongation above 15 pct remains even after rolling at the lowest applied temperature of 773 K. The strength properties, i.e., the ranges of r 0.2 and UTS obtained in the present warm to hot rolled steel samples, are almost the same with those obtained in other work-hardened high-Mn TWIP steels, although plasticity of the present steel samples is not so large. [35][36][37][38][39] On the other hand, other multiphase medium-Mn steels commonly exhibit poorer plasticity. [9] It is clearly seen in Figure 9 that all the warm-to-hot rolled steel samples are characterized by almost the same strain hardening behavior upon the subsequent tensile tests at room temperature.…”
Section: Tensile Testsmentioning
confidence: 99%
“…Another interesting point to be noted in Figure 9 is the maximal stresses, which are limited by a level of 1200 to 1300 MPa, except the initial sample with a coarse grained microstructure after hot rolling at 1423 K. Similar strength limitation has been reported for various high-Mn TWIP steels processed by cold or hot working. [35][36][37][38][39] Such upper limit of the flow stress was considered being associated with a maximal strain hardening, which could be assisted by deformation twinning. [35] In this case, further straining beyond the twinning-assisted dislocation storage should inevitably proceed with a localization of plastic flow leading to necking and failure.…”
Section: Tensile Testsmentioning
confidence: 99%